Analisis Persepsi Jamaah Masjid di Kecamatan Gondokusuman Terhadap Keputusan Penggunaan QRIS - Hafifuddin Hafifuddin; Rofiul Wahyudi (Dinamis : Journal of Islamic Management and Bussiness, 2022)
This study aims to analyze the mosque congregation's decision to use QRIS against ZIS and to find out which variable influences the decision to use QRIS against ZIS. The research method used is quantitative. Respondents in this study were mosque congregations in the Gondokusuman sub-district. The population in this study were all mosques in Gondokusuman District. The sampling technique used was purposive sampling, and a sample of 100 respondents was obtained. The data collection technique uses a questionnaire distributed to mosque congregations carrying out non-cash transactions in the form of QRIS. Methods of data analysis using multiple linear regression analysis, hypothesis testing (t-test and F test), and test the coefficient of determination (R2). The results of this study show that partially and simultaneously, the convenience variable and the benefits variable have a positive and significant effect on the decision of the congregation of mosques in the Gondokusuman sub-district to use QRIS as a ZIS transaction tool. Simultaneously, the convenience variable and benefits variable influence the decisions of mosque congregations in the Gondokusuman sub-district using QRIS as a tool for ZIS transactions with an effect size of 26.6%.